Familia 2011
DOI: 10.36576/summa.30594
|View full text |Cite
|
Sign up to set email alerts
|

III. Educación y valores en las Familias Monoparentales

Abstract: Along this article, the author focuses his attention, among all the types of family existing, on the monoparental ones, as this family structure has aroused troubles related to the domains and difficulties of these family structures: Will the mother be able to harmonize her working responsibilities with the family demands? What type of help would she need in a more immediate way? Would she need help (social or familiar) to assume all those responsibilities? Would she offer a suitable and educative family envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…At the end of the 1980s, a series of laws were enacted in Spain enabling single women to become mothers through either adoption or ART. It may be that this legal support, along with the feminist ideology underlying it, fostered the process of empowerment and self-legitimation observed among Spanish single mothers by choice (González et al, 2011), which is similar to that observed among women in other countries also (Ben-Ari & Weinberg-Kurnik, 2007; Bock, 2000). Most likely, the security afforded by a well-founded sense of competence and legitimacy has enhanced single women’s parenting and contributed to the healthy development of their children.…”
Section: Discussionmentioning
confidence: 57%
“…At the end of the 1980s, a series of laws were enacted in Spain enabling single women to become mothers through either adoption or ART. It may be that this legal support, along with the feminist ideology underlying it, fostered the process of empowerment and self-legitimation observed among Spanish single mothers by choice (González et al, 2011), which is similar to that observed among women in other countries also (Ben-Ari & Weinberg-Kurnik, 2007; Bock, 2000). Most likely, the security afforded by a well-founded sense of competence and legitimacy has enhanced single women’s parenting and contributed to the healthy development of their children.…”
Section: Discussionmentioning
confidence: 57%
“…En la mayoría de estos casos, son familias con bastantes miembros, con una media de 3 a 4 hijos, y en un 30 o 40% de los casos, son familias monoparentales, a cargo de mujeres solas (Rodríguez, Camacho, Rodrigo, Martín y Máiquez, 2006;Rodrigo, Correa, Máiquez, Martín y Rodríguez, 2006). Estas familias presentan, además, precariedad económica que hace que constantemente dependan de las ayudas sociales (Arruabarrena y De Paúl, 2002;González Ortiz, 2011). Esta situación suele tener su origen en la inestabilidad laboral, en las pésimas condiciones del puesto de trabajo (Arruabarrena y De Paúl, 2002;Moreno, 2002) y en el desempleo de los responsables de dichas familias (Rodrigo et al 2006).…”
Section: Perfil De Las Familias En Situación De Riesgounclassified
“…Si entendemos que el bienestar familiar no sólo es el resultado de una estructura determinada, sino también fruto de una dinámica de funcionamiento y de una amplia y compleja red de relaciones, podremos entender que en las familias monoparentales también "laten" valores que sustentan la conducta de los que viven en este tipo de familias (González Ortiz, J. J., 2008).…”
Section: Los Valores En Las Familias Monoparentalesunclassified